Applications of control theory to economic analysis - Pitchford, J. D.; Turnovsky, Stephen J. (Amsterdam ; New York : North-Holland Pub. Co. ; New York : sole distributors for the U.S.A. and Canada, Elsevier/North-Holland, 1977)
The term economic analysis as used in the title of the series has been adopted because it covers both the activities of the theoretical economist and the research worker. This volume covers dynamic applications, illustrate the wide range of economic problems to which control theory may be applied.
Includes bibliographical references.
rpm 21/06/2017
Loans
Keywords: Economics, Mathematical; Economics. Applications of control theory; Economics $1 (BApplications of control theory mathematics.s; Control theory; Economics $1 (Bapplications $1 (Bcontrol theory.s